2013
DOI: 10.1088/1475-7516/2013/03/032
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum for inflation models with quantum and thermal noises

Abstract: We determine the power spectrum for inflation models covering all regimes from cold (isentropic) to warm (nonisentropic) inflation. We work in the context of the stochastic inflation approach, which can nicely describe both types of inflationary regimes concomitantly. A throughout analysis is carried out to determine the allowed parameter space for simple single field polynomial chaotic inflation models that is consistent with the most recent cosmological data from the nine-year Wilkinson Microwave Anisotropy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
181
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(196 citation statements)
references
References 93 publications
13
181
2
Order By: Relevance
“…[51][52][53][54][55][56][57]. In this form, from the definition of the parameter ε, the value of the scalar field φ 1 as a result is…”
Section: B[t] Denotes the Incomplete Beta Function [91] Defined Asmentioning
confidence: 99%
See 1 more Smart Citation
“…[51][52][53][54][55][56][57]. In this form, from the definition of the parameter ε, the value of the scalar field φ 1 as a result is…”
Section: B[t] Denotes the Incomplete Beta Function [91] Defined Asmentioning
confidence: 99%
“…The model of intermediate inflation was in the beginning formulated as an exact solution to the background equations, nevertheless, this model may be studied under the slowroll approximation together with the cosmological perturbations. In particular, under the slow-roll analysis, the effective potential is a power-law type, and the scalar spectral index becomes n s ∼ 1, and exactly n s = 1 (Harrizon-Zel'dovich spectrum) for the special value f = 2/3 [51][52][53][54][55][56][57]. In the same way, the tensor-to-scalar ratio r becomes r = 0 [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…If the inflaton fluctuations are also in thermal equilibrium with the thermal bath there will again be a coth term in the density perturbation spectrum, as seen, for example, in Refs. [29][30][31]. In both thermal and warm inflation, the presence of the coth term would affect density perturbations with large power on the relevant large scales, as in Ref.…”
Section: Discussionmentioning
confidence: 93%
“…[8][9][10][11]). The greatest appeal of warm inflation lies perhaps in the fact that thermal inflaton fluctuations are directly sourced by dissipative processes, changing the form of the primordial spectrum of curvature perturbations and thus providing a unique observational window into the particle physics behind inflation [11][12][13][14][15][16][17][18]. In addition, we have recently shown that warm inflation can be consistently realized in a simple quantum field theory framework requiring very few fields, the Warm Little Inflaton scenario [19], where the required flatness of the inflaton potential is not spoiled by thermal effects (see also refs.…”
Section: Jhep02(2018)063mentioning
confidence: 99%